Antagonism of Azole Activity against Candida albicans following Induction of Multidrug Resistance Genes by Selected Antimicrobial Agents - Henry, Karl W. (American Society for Microbiology, 1999)
Antifungal azoles (e.g., fluconazole) are widely used for prophylaxis or treatment of Candida albicans infections in immunocompromised individuals, such as those with AIDS. These individuals are frequently treated with a variety of additional antimicrobial agents. Potential interactions between three azoles and 16 unrelated drugs (antiviral, antibacterial, antifungal, and antiprotozoal agents) were examined in vitro. Two compounds, tested at concentrations achievable in serum, demonstrated an antagonistic effect on azole activity against C. albicans. At fluconazole concentrations two to four times the 50% inhibitory concentration, C. albicans growth (relative to treatment with fluconazole alone) increased 3- to 18-fold in the presence of albendazole (2 μg/ml) or sulfadiazine (50 μg/ml). Antagonism (3- to 78-fold) of ketoconazole and itraconazole activity by these compounds was also observed. Since azole resistance has been correlated with overexpression of genes encoding efflux proteins, we hypothesized that antagonism results from drug-induced overexpression of these same genes. Indeed, brief incubation of C. albicans with albendazole or sulfadiazine resulted in a 3-to->10-fold increase in RNAs encoding multidrug transporter Cdr1p or Cdr2p. Zidovudine, trimethoprim, and isoniazid, which were not antagonistic with azoles, did not induce these RNAs. Fluphenazine, a known substrate for Cdr1p and Cdr2p, strongly induced their RNAs and, consistent with our hypothesis, strongly antagonized azole activity. Finally, antagonism was shown to require a functional Cdr1p. The possibility that azole activity against C. albicans is antagonized in vivo as well as in vitro in the presence of albendazole and sulfadiazine warrants investigation. Drug-induced overexpression of efflux proteins represents a new and potentially general mechanism for drug antagonism.